INTERNALISASI NILAI AKHLAKUL KARIMAH PADA SISWA KELAS XI MADRASAH ALIYAH SWASTA TARBIAH ISLAMIYAH HAMPARAN PERAK KABUPATEN DELI SERDANG - Malik, Muklis; Lubis, Sakban; Imran, Zulfi; Devina, Amanda (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this research is to describe and analyze in depth the efforts to internalize Akhlakul Karimah (noble character) among the 11th-grade students of the Tarbiah Islamiyah Private Madrasah Aliyah in the Hamparan Perak District, Deli Serdang Regency. The process of internalizing noble character at Madrasah Aliyah Tarbiyah Islamiyah Hamparan Perak will be detailed, including the methods used and the factors that support and hinder its implementation. This research is qualitative in nature, with the background set at Madrasah Aliyah Tarbiyah Islamiyah. Data will be collected through interviews, observations, and documentation. Data analysis will be conducted using descriptive analytical methods to derive conclusions from the meaning of the collected data. The research findings indicate that the implementation of character internalization at Madrasah Aliyah Tarbiyah Islamiyah Hamparan Perak has been successful as expected, reflected in the daily behaviors of students, including courteous communication with teachers, peers, and the surrounding community. Supporting factors include the collaboration between the madrasah and the boarding school, as well as cooperation with subject teachers and class guardians. Meanwhile, inhibiting factors include a lack of support from families and the environment, as well as peer influence among students.